The Effect of Cycloplegia on the Ocular Biometric and Anterior Segment Parameters: A Cross-Sectional Study - Hamed Momeni-Moghaddam; Nasim Maddah; James S. Wolffsohn; Mohammad Etezad-Razavi; Siamak Zarei-Ghanavati; Amir Akhavan Rezayat; Majid Moshirfar (Ophthalmology and Therapy, 2019)
Abstract Introduction To evaluate the effects of cycloplegia on the biometric components and anterior segment parameters of the eye. Methods In this cross-sectional study, changes to axial length (AL), anterior chamber depth (ACD) lens thickness, anterior chamber angle (ACA) and volume, corneal thickness in the pupil center (PC), corneal curvature (CC) and white-to-white (WTW) following cycloplegia induced by tropicamide 1% in 42 eyes of patients aged 23–58 years were assessed. Biometric components and anterior segment parameters were measured using an IOLMaster 700 (Carl Zeiss Meditec, Jena, Germany) and a Pentacam HR (Oculus Optikgeräte GmbH, Wetzlar, Germany), respectively. Results Significant statistical changes in ACD (increased by 0.06 ± 0.05 mm; p < 0.001), anterior chamber volume (increased by 15.19 ± 10.32 mm3; p < 0.001), ACA (decreased by 2.18 ± 10.20°; p = 0.029) and lens thickness (decreased by 0.02 ± 0.03 mm; p < 0.001) were observed post-cycloplegia, while the changes in CC, corneal thickness in the PC, WTW and AL were not statistically different (p > 0.05). Also, a significant inferior displacement of the PC along the vertical axes was seen (p = 0.020). Conclusion Cycloplegia resulted in a deeper ACD and thinner lens thickness. These changes should be considered in determining intraocular lens (IOL) power to prevent refractive surprises in cataract surgery and also in the phakic IOL implantation.